Penurunan Waktu Siklus Proses Cetak Injeksi Produk Tutup Plastik Melalui Simulasi Moldflow - Arifin, Uma Fadzilia; Suci Rahayu (Universitas Negeri Gorontalo, 2023)
The cycle time is the integral factors of the production process. The higher the cycle time, the longer the time for the production process so as to reduce the efficiency and effectiveness of the production process. Plastic cap production uses an injection molding machine. The time required to produce a plastic cap is relatively high is about 33 seconds. This study aims to reduce the cycle time of plastic caps production during the injection molding process through simulation using Autodesk Moldflow software. Simulation was conducted to determine the optimal temperature parameter where other parameters are kept constant. The design of this simulation experiment used the Taguchi method with an orthogonal array as the simulation matrix. The simulation results was analyzed using the Minitab 19 software to determine the response value of the S/N ratio in the smaller is better category. Based on the value of the S/N ratio, the optimal combination of process temperature parameters is 180°C for melt temperature and 32°C for mold temperature to be able to reduce cycle time by 9.34 seconds. The simulation results show that the cycle time required for plastic cap production is 23.66 seconds.